Optimisation of acid fast smears for the direct detection of mycobacteria in clinical samples - Murray, S J (Copyright 2003 Journal of Clinical Pathology, 2003)
Aims: Despite its long history, the acid fast smear remains unstandardised. Technical variations in both the preparation of clinical material and subsequent staining mean that smear sensitivity relative to culture may vary from 50% to over 80%. This study assessed the sensitivity of acid fast microscopy at each of five stages of sample preparation and by both commonly used staining methods. Methods: Sputum samples thought for varying reasons to be highly likely to be culture positive were used to prepare a series of smears in which the effects of digestion (liquefaction), concentration (centrifugation), and decontamination (sodium hydroxide) could be assessed, together with a comparison of staining by the auramine/phenol and Ziehl-Neelsen techniques. Results: The most effective method for the demonstration of acid fast organisms in sputum was found to be an auramine phenol stain applied to a liquefied, concentrated sample and examined before the decontamination process. Conclusions: The auramine phenol stain applied to a liquefied, concentrated sample and examined before the decontamination process is the most effective method for the demonstration of acid fast organisms in sputum.